Kemiskinan Dan Bagaimana Memeranginya - Tri Wahyu R. (Universitas Wahid Hasyim, 2009)
The problem of poverty was crusial for all countries on the world. The data of poverty is very important to support strategies for decreasing poverty and will be instrument by policy maker. In other, the data of poverty and the poor can be using to formulating policy and get to target of policy. All of strategy was goal of improving welfare.Keywords: poverty and the poor